Cloning and sequence analysis of S1 gene of isolate J of avian nephropathogenic infectious bronchitis virus - ZHOU Ji-yong; HE Yong-qiang (浙江大学学报. 农业与生命科学版, 2000)
cDNA of S1 gene of isolate J of avian nephropathogenic infectious bronchitis virus (IBV) isolated from Zhejiang province was amplified by reverse transcription-polymerase chain reaction with special primers and cloned into plasmid pBluescript SK. The recombinants were identified by digestion of restriction enzyme BamHI, Hind Ⅲ and PCR-amplification, while the recombinants were sequenced. The results show that cDNA of S1 gene of isolate J of IBV was composed of 1 731 nucleotides encoding a polypeptide of 576 amino acids. Nucleotide homogeneity of S1 gene of IBV-J isolate with S1 genes of other IBV strains M41, H120, Beaudette, Beijing, D41, Gray, 4/91 ranged from 82.73% to 78.42%. S1 gene of IBV-J isolate existed much point mutation, as well as gene insert and gene deletion. Evolution analysis indicated that IBV-J isolate was far relation to the other strains of IBV. These results suggested that IBV-J isolate was a new variant of IBV.